Total cholesterol level and its associated factors among hospitalized elderly: a cross-sectional study - Hambali, Noor Azleen; Omar, Noraida; Md. Yusop, Nor Baizura (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: The total cholesterol level of hospitalized elderly should be monitored as the long-term consequence of hypercholesterolemia is the development of cardiovascular diseases. This study aimed to determine the total cholesterol level among hospitalized elderly and its associated factors in Hospital Serdang, Selangor. Methods: A total of 115 hospitalized elderly aged 60 and above have participated in the study. Data on socio-demographic characteristics, medical backgrounds, anthropometric measurements, biochemical, dietary intake, malnutrition risk, lifestyle, and total cholesterol level were obtained through face-to-face interviews and physical examination. Dietary intake was assessed using the two-day diet history. Mini Nutritional Assessment (MNA-SF) was used to determine the malnutrition risk of the subjects. Results: The prevalence of hypercholesterolemia among the subjects was 29.6% with a mean value of 4.08 ± 1.51 mmol/L. Comorbidities specifically dyslipidemia (χ2 =14.291, p≤0.0005), and other comorbidities (χ2 =7.843, p=0.005), waist circumference (r=0.199, p=0.033), LDL-C (r=0.455, p≤0.0005), triglyceride (r=0.459, p≤0.0005), fasting blood glucose (r=0.386, p≤0.0005), carbohydrate (r=-0.333, p≤0.0005), fat (r=0.327, p≤0.0005), saturated fat (r=0.304, p=0.001), PUFA (r=0.275, p=0.003), MUFA (r=0.327, p≤0.0005), sodium (r=0.211, p=0.024), and duration of physical activity (r=-0.287, p=0.002) were found to be significantly associated with the total cholesterol level. Meanwhile, other variables were found not to be associated. Conclusion: Current study reported the prevalence of hypercholesterolemia of 29.6%. Comorbidities specifically dyslipidemia and other comorbidities, waist circumference, LDL-C, TG, fasting blood glucose, carbohydrate, fat, saturated fat, PUFA, MUFA, sodium, and duration of physical activity were significantly associated with the total cholesterol level. Meanwhile, other variables were not significantly associated.